Morphometric Characteristics of Lymphoid Organs and Serological Studies in Egg-Laying Birds Using an Immunomodulator, Vitamins and Amino Acids - Cortés Machado, Luz; Villamarín Jurado, Sonia (Spei Domus, 2013)
The first target organ damaged by infectious bursa virus disease (ibvd) is the bursa, manifested in severe depletion of the B cells. However, this depletion depends on the regions of the lymphoid organs involved in the infection. Based on the existing relationship between the morphometry of the lymphoid organs and the inmunocompetence of the birds, it is interesting to observe possible effects from immunomodulators, vitamins and amino acids on the immune response for Gumboro(ibd) disease. In the lymphoid organs (swindle, spleen and bursa), the following parameters were evaluated until the first 8 weeks of age: weight of the bird, weight of each organ and serology for the Gumboro entity at 5 and 9 weeks. They were divided into 2 groups with the same handling (accommodation, feed and environment), but with different treatments. Group A (test J8), consisting of 55,062 birds, was given an immunomodulators during the first 3 days of life and 2 days after each application of the Gumboro vaccine. The vitamins and amino acids were administered from the fourth to the sixth day and 2 days following the change in food (pre-initiation and initiation phases). Group B (Control j7), consisting of 55,484 birds, was administered liver protector. Serological samples were taken at 5 and 9 weeks of age. In conclusion, the use of the immunomodulator, vitamins and amino acids during the reception protocol produces benefits observed in better consumption, weight, uniformity and proper development of the immune system.